Urban Sufism: The New Fluorishing Vivacity of Contemporary Indonesian Islam - Dadi Darmadi (Studia Islamika, 2001)
Indonesia has maintained strong ties through social, economic and religious reciprocities with the heartland of Islam and corresponding to similar developments in other part of the Muslim world. As the largest Muslim country in the world, Indonesia is commonly known as a unique site for various forms of sociological representation of Islamic beliefs. Since at least the 13th century, Islam has been acknowledged as a formal religion embraced by diverse communities from the coastal areas to the rural interiors of the archipelago. One of the most profound and distinctive practices accepted by many Indonesian Muslims is the Islamic mystical expression, known as Sufism. Due to its distinctive nature and teachings, Sufism has often been depicted AS "low" or popular Islamic tradition vis a vis "high" and pristine Shari'ah-oriented Islamic tradition.DOI: 10.15408/sdi.v8i1.700